Aid, institutions and development - Chakravarti, Ashok (New Delhi, 2005)
In order for aid to have a significant impact on development, the author of this book argues that there should be more recognition of the role economic and political governance can play in achieving positive and sustainable development outcomes. Using the latest empirical findings on aid and growth, this book reveals how good governance can be achieved by radically restructuring the international aid architecture.
Keywords: Poverty